Psikologi Lintas Budaya dalam Belajar dan Pengembangan - Nur, Ahmad; Ahmadin, Ahmadin; Ibrahim, Ibrahim (Indo-MathEdu Intellectuals Journal, 2025)
This article examines the role of cross-cultural psychology in education through a literature review using a qualitative descriptive method. Data sources were obtained from various national scientific journals and academic books discussing cross-cultural psychology, multicultural education, and educational psychology. The analysis was conducted through stages of data reduction, synthesis of findings, and interpretation of conceptual meanings to construct an integrative framework. The findings reveal that cultural adaptation, intercultural communication, and multicultural education are key components that influence the quality of learning in diverse environments. Cultural adaptation enables students to adjust to differences in values and ways of thinking, while cross-cultural communication helps foster more empathetic interactions and reduces potential conflict. Additionally, strengthening multicultural character through the cultivation of tolerance, cooperation, and appreciation for diversity supports students in navigating life within a pluralistic society. Overall, cross-cultural psychology serves not only as a theoretical foundation but also as a practical guide for creating learning environments that are inclusive, adaptive, and sensitive to cultural diversity. This approach contributes to shaping learners who are open-minded, multicultural, and prepared to live harmoniously amid global change.